First Principles Investigation of the Effect of Vanadium Doping on Electronic Structure, Magnetic, and Optical Properties of Graphene–Boron Nitride Heterostructure - Shalisho, Berhanu Aymalo; Shanko, Markos Meskele; Hailemariam, Sintayehu Mekonnen (Advances in condensed matter physics, 2025)
We investigate the effect of vanadium (V) doping on the electronic, magnetic, and optical properties of the graphene/hexagonal boron nitride (G/h‐BN) heterostructure using spin‐polarized density functional theory (DFT). Defect formation energy calculations show that the V atom prefers substituting boron (B) sites over nitrogen (N) sites and the V‐doped G/h‐BN heterostructures are energetically stable. The lattice constant of the V‐doped G/h‐BN increases due to the larger atomic radius of the V atom. The electronic band structure analysis reveals that the band gap of G/h‐BN increases from 0.053 to 1.25 eV with 2.08% V doping. The total density of states (TDOSs) analysis indicates a transition from paramagnetic to ferromagnetic (FM) behavior upon V doping. Moreover, the magnetic energy ( ∆E ) calculations show that two V dopants in G/h‐BN favor FM interactions, although the energy decreases as the distance between dopants increases. Using mean‐field theory combined with spin‐polarized DFT, we estimate the corrected FM transition temperature ( T c ) to be 457 K for 4.16% V doping in G/h‐BN. Additionally, optical absorption analysis shows a significant enhancement in the absorption coefficient in the visible region due to V doping. This study offers insights into the potential use of V‐doped G/h‐BN for spintronic and optoelectronic applications, subject to further theoretical and experimental validation.